DNA origami/gold nanorod hybrid nanostructures for the circumvention of drug resistance. Issue 23 (5th June 2017) - Song, Linlin; Jiang, Qiao; Liu, Jianbing; Li, Na; Liu, Qing; Dai, Luru; Gao, Yuan; Liu, Weili; Liu, Dongsheng; Ding, Baoquan
Abstract : DNA origami works as a multifunctional platform integrating a chemotherapeutic drug (doxorubicin), gold nanorods and a tumour-specific aptamer MUC-1, to realize the effective circumvention of drug resistance. Abstract : We herein demonstrate that DNA origami can work as a multifunctional platform integrating a chemotherapeutic drug (doxorubicin), gold nanorods and a tumour-specific aptamer MUC-1, to realize the effective circumvention of drug resistance. Doxorubicin (DOX) was loaded efficiently onto DNA origami through base pair intercalation and surface-modified gold nanorods (AuNRs) were assembled onto the DNA origami through DNA hybridization. Due to the active targeting effect of the assembled aptamers, the multifunctional nanostructures achieved increased cellular internalization of DOX and AuNRs. Upon near-infrared (NIR) laser irradiation, the P-glycoprotein (multidrug resistance pump) expression of multidrug resistant MCF-7 (MCF-7/ADR) cells was down-regulated, achieving the synergistically chemotherapeutic (DOX) and photothermal (AuNRs) effects.